Direct Optimization of an Automotive Sheet Metal Part Using ANSYS - Khalid, Usman; Mustafa, Othman Mohammad Ahmed; Naeem, Muhammad Ali; Alkhateeb, Mohammad Yousef Mohammad; Awad, Basil Marwan Abed Eljaber (International Journal of Engineering and Management Sciences, 2020)
Optimization of automotive parts nowadays is mainly used to design lightweight and cost-effective vehicle parts in order to improve the cost and efficiency. In this research, a sheet metal part was taken into consideration and optimized using direct optimization module in ANSYS to evaluate the process. An initial Finite Element Analysis (FEA) was done on the sheet metal part by adding forces and constraints in order to initiate direct optimization. The purpose of the optimization is to minimize the mass of the sheet metal part and maintaining a certain Factor of Safety (FOS) by automatically modifying the sheet thickness and the dimension of the side holes. As a result, the best candidate point with 23% mass reduction was found which complied with FOS value was selected for optimal geometry.